2009
DOI: 10.1080/13825580802691763
|View full text |Cite
|
Sign up to set email alerts
|

Can Computer Familiarity Regulate the Benefits of Computer-based Memory Training in Normal Aging? A Study with an Italian Sample of Older Adults

Abstract: In this study, we investigated whether computer familiarity could regulate the efficacy of a computer-based memory training intervention in an Italian sample of older adults. Participants were randomly assigned to either the training or the waiting-list control group and were tested on four computerized neuropsychological memory tasks and one paper-pencil task. Computer familiarity measures included a computer questionnaire, reaction times in a pointing task and mouse use ability. Only the training group was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 39 publications
2
28
0
2
Order By: Relevance
“…Thus, our finding that gains in non-verbal long-term memory, attention and set-shifting was predicted by female gender needs further investigation. The fact that higher age was a negative predictor for gains in (non-verbal) memory and attention is concordant with the notion that higher age is regarded to be associated with less brain and cognitive plasticity [25] and with other findings that younger age predict better training outcome of cognitive or memory training [69] The inconsistent results regarding technology commitment as a predictor for gains in figural memory, but losses in executive functions and speed of processing are hard to interpret-even more so when the results of [29] are taken into account that computer familiarity (although a slightly different construct) was not predictive at all for the success of computer-based memory…”
Section: E Kalbe Et Al Healthsupporting
confidence: 47%
See 1 more Smart Citation
“…Thus, our finding that gains in non-verbal long-term memory, attention and set-shifting was predicted by female gender needs further investigation. The fact that higher age was a negative predictor for gains in (non-verbal) memory and attention is concordant with the notion that higher age is regarded to be associated with less brain and cognitive plasticity [25] and with other findings that younger age predict better training outcome of cognitive or memory training [69] The inconsistent results regarding technology commitment as a predictor for gains in figural memory, but losses in executive functions and speed of processing are hard to interpret-even more so when the results of [29] are taken into account that computer familiarity (although a slightly different construct) was not predictive at all for the success of computer-based memory…”
Section: E Kalbe Et Al Healthsupporting
confidence: 47%
“…Indications that computer familiarity does not seem to be predictive for success of computer-based memory training [29] suggest that CCT has the potential to be a practical and viable method for delivering interventions, even for elderly people without digital familiarity. In patients with cognitive impairment (mild cognitive impairment or dementia), the outcomes of cognitive interventions are related not only to baseline cognitive performance [26] [30] baseline functional abilities and behavioural symptoms [31], but also age [32] [33], sex [17] [32]…”
Section: E Kalbe Et Almentioning
confidence: 99%
“…In individual studies (table 1), significant improvements were reported for cognitive training compared to no intervention in 19 of 26 memory outcome measures (Bailey et al, 2010;Bottiroli and Cavallini, 2009;Buiza et al, 2008;Cavallini et al, 2010;Cheng et al, 2012;Craik et al, 2007;Edwards et al, 2002;Fairchild and Scogin, 2010;Hastings and West, 2009;Jackson et al, 2012;Mahncke et al, 2006;Valentijn et al, 2005), in seven out of 16 measures of executive function (Ball et al, 2002;Buiza et al, 2008;Cheng et al, 2012;Craik et al, 2007;Edwards et al, 2002;Jackson et al, 2012;Mahncke et al, 2006;Margrett and Willis, 2006), and on both composite measures of cognitive function (Cheng et al, 2012;Mahncke et al, 2006). One trial found that reasoning training resulted in less self-reported decline in everyday functioning compared to control (Ball et al, 2002;Willis et al, 2006).…”
Section: Cognitive Training Versus 'No Intervention'mentioning
confidence: 99%
“…For secondary outcomes, significant improvements were reported for training versus control in four out of six measures of subjective cognitive performance (Fairchild and Scogin, 2010;Hastings and West, 2009;Valentijn et al, 2005). Transfer of training effects were recorded in five out of seven trials: four reported transfer to untrained tasks within the same domain (Bottiroli and Cavallini, 2009;Cavallini et al, 2010;Cheng et al, 2012;Mahncke et al, 2006), one to other cognitive domains (Cheng et al, 2012), and one to everyday functioning (Ball et al, 2002). All seven trials that included follow-up assessments reported maintenance of training effects (Ball et al, 2002;Buiza et al, 2008;Cheng et al, 2012;Craik et al, 2007; Hastings and West, 2009;Mahncke et al, 2006;Valentijn et al, 2005).…”
Section: Cognitive Training Versus 'No Intervention'mentioning
confidence: 99%
“…A growing number of studies have examined the training benefits of executive function (Karbach and Verhaeghen, 2014 for a review; Kelly et al, 2014 for a review) and associative memory (Derwinger et al, 2003; Bottiroli and Cavallini, 2009; Gross et al, 2012 for a review). It has also been reported that cognitive training, combined with multiple components, produced a broader effect on multiple cognitive domains than single cognitive training (Cheng et al, 2012; Walton et al, 2014).…”
Section: Introductionmentioning
confidence: 99%